2021
DOI: 10.1016/j.cbi.2020.109300
|View full text |Cite
|
Sign up to set email alerts
|

Plant isoquinoline alkaloids as potential neurodrugs: A comparative study of the effects of benzo[c]phenanthridine and berberine-based compounds on β-amyloid aggregation

Abstract: Herein we present a comparative study of the effects of isoquinoline alkaloids belonging to benzo [ c ]phenanthridine and berberine families on β-amyloid aggregation. Results obtained using a Thioflavine T (ThT) fluorescence assay and circular dichroism (CD) spectroscopy suggested that the benzo [ c ]phenanthridine nucleus, present in both sanguinarine and chelerythrine molecules, was directly involved in an inhibitory effect of Aβ 1–42 aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 102 publications
0
20
0
Order By: Relevance
“…In recent years, naturally derived alkaloids have been involved in the management of neurodegenerative diseases and have shown high potential in inhibiting amyloid aggregation [ 36 , 39 , 48 , 49 ]. Given the importance of seeds in the pathological amyloid formation in vitro and in vivo [ 2 , 50 , 51 , 52 , 53 ], we screened nine Chinese herbal alkaloid compounds for their effect on seeded induced α-syn aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, naturally derived alkaloids have been involved in the management of neurodegenerative diseases and have shown high potential in inhibiting amyloid aggregation [ 36 , 39 , 48 , 49 ]. Given the importance of seeds in the pathological amyloid formation in vitro and in vivo [ 2 , 50 , 51 , 52 , 53 ], we screened nine Chinese herbal alkaloid compounds for their effect on seeded induced α-syn aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular Docking. In order to carry out the molecular docking studies, we obtained the most representative monomeric model of the protein that were reported by Marasco and co-workers 55 and were based on the extensive computational studies of Krupa and coworkers 56 involving S-shape and U-shape fibril models (PDB codes 2LMN and 2MXU).…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Second, screen natural substances with multiple actions against various insults/mechanisms involved in AD. Several natural compounds, such as chelerythrine ( Marasco et al, 2021 ), chalcone ( Thapa et al, 2021 ), coumarin ( Li et al, 2022 ), huprine ( Serrano et al, 2016 ), curcumin ( Mukherjee et al, 2021 ), rhein ( Li et al, 2019 ), berberine ( Akbar et al, 2021 ), and resveratrol derivatives ( Akbar et al, 2021 ), have shown such potential and warrant further studies for AD drug development ( Noori et al, 2021 ). The new drug GV-971 ( Xiao et al, 2021 ) belongs to this category.…”
Section: Multi-targets: An Unconventional Strategy For Alzheimer’s Di...mentioning
confidence: 99%